View from the inside. The images of the city in the “black series” documentary films in Poland in the 1950s - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article analyses the particular interest that the documentary filmmakers of the late 1950s had in the architectural and urban issues. The reasons for this phenomenon are situated in several plans: they refer to the image of reconstruction from the war devastation and the reaction to its falsification in the period of socialist realism. They refer to the social interests of the filmmakers and to the strategy of metaphorising and allegorising the images of the city, which was handy in the times of censorship as it extended meanings and applied non-literality. The article analyses various film incarnations of this phenomenon.